Plasmonic Nanostructures for Nano-Scale Bio-Sensing - Chung, Taerin (Molecular Diversity Preservation International (MDPI), 2011)
The optical properties of various nanostructures have been widely adopted for biological detection, from DNA sequencing to nano-scale single molecule biological function measurements. In particular, by employing localized surface plasmon resonance (LSPR), we can expect distinguished sensing performance with high sensitivity and resolution. This indicates that nano-scale detections can be realized by using the shift of resonance wavelength of LSPR in response to the refractive index change. In this paper, we overview various plasmonic nanostructures as potential sensing components. The qualitative descriptions of plasmonic nanostructures are supported by the physical phenomena such as plasmonic hybridization and Fano resonance. We present guidelines for designing specific nanostructures with regard to wavelength range and target sensing materials.